Macrophage activation syndrome in an inadequately treated patient with systemic onset juvenile idiopathic arthritis - Juneja, M; Jain, R; Mishra, D (Kathmandu University Medical Journal, 2010)
Macrophage activation syndrome is a rare and potentially life threatening complication of childhood rheumatic disorders. It is described most commonly with systemic onset juvenile idiopathic arthritis (soJIA). The major clinical manifestations are non-remitting fever, hepatosplenomegaly, lymphadenopathy, bleeding diathesis, altered mental status and rash and may mimic a flare of soJIA. The characteristic laboratory findings are leucopenia, thrombocytopenia and dramatic elevation of urinary β2 microglobulin. Corticosteroids and cyclosporine are the drugs commonly used in its management. Early diagnosis and prompt treatment can be life saving. We report a case of 12 year old female child with inadequately treated systemic onset juvenile idiopathic arthritis who developed fatal macrophage activation syndrome. The diagnosis and management of macrophage activation syndrome are discussed. Key words: Macrophage activation syndrome; systemic onset juvenile idiopathic arthritis; leucopenia; children. DOI: 10.3126/kumj.v7i4.2764 Kathmandu University Medical Journal (2009) Vol.7, No.4 Issue 28, 411-413